Adsorption of phosphate from aqueous solution by Zr(IV)‐crosslinked quaternized chitosan/bentonite composite. Issue 1 (11th June 2017) - Wang, Jing; Liu, Yanping; Hu, Pan; Huang, Ruihua
Abstract : Zr(IV)‐crosslinked HACC/BT composite was prepared and characterized by FTIR, XRD, and SEM techniques. This composite was applied for the adsorption of phosphate ions from aqueous solutions. The factors of various parameters including adsorbent dosage, pH, competing anions, and contact time affecting phosphate adsorption were studied. The adsorption isotherm data were well described by both Langmuir and Freundlich models, and the maximum monolayer adsorption capacity for phosphate was estimated to be 65.35 mg/g at 293 K and natural pH. Kinetic experiments demonstrated that phosphate adsorption fitted better with a pseudo‐second‐order model. The adsorption mechanisms included the electrostatic interaction, ligand exchange, and hydrogen bond formation between phosphate and this composite. Thermodynamic parameters confirmed the exothermic and spontaneous nature of the phosphate adsorption. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 267–275, 2018